1998
DOI: 10.5006/1.3284827
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Copper on Active Dissolution and Pitting Corrosion of 25% Cr Duplex Stainless Steels

Abstract: Electrochemical studies were made of the influence of Cu on pitting behavior and active dissolution of 25% Cr duplex stainless steels (DSS) in chloride-containing neutral and acid solutions. Alloys with increased Cu content showed higher pitting potentials (E p ) in 1 M hydrochloric acid (HCl) and 3.5% sodium chloride (NaCl) solutions. In HCl, the current density in the active state also was lower for the Cu-containing alloys. However, the critical pitting temperature (CPT) in ferric chloride (FeCl 3 ) was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 23 publications
0
14
0
1
Order By: Relevance
“…Researchers have found that Cu additions to SDSS increase pitting potential and overall localized corrosion resistance to halide environments. 61,64 It may be questioned, therefore, whether the difference in Cu could be responsible for the outstanding resistance of UNS S39274.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have found that Cu additions to SDSS increase pitting potential and overall localized corrosion resistance to halide environments. 61,64 It may be questioned, therefore, whether the difference in Cu could be responsible for the outstanding resistance of UNS S39274.…”
Section: Discussionmentioning
confidence: 99%
“…Selective phase dissolution is common in DSS. [61][62] The preferential attack depends primarily on the partitioning of alloying elements to austenite or ferrite, 61,[63][64] which in turn defines the critical localized corrosion potential of the phase (and the local PRE). 65 The phase with the lowest critical localized corrosion potential dissolves first and determines the alloy's overall pitting or crevice potentials.…”
Section: Electrochemical Critical Pitting Temperature As Per Astm G150mentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12][13][14][15] One approach to improve the localized corrosion resistance of these alloys is to add small amounts of Cu. The effect of Cu addition on corrosion resistance, particularly localized corrosion, has been studied in detail for stainless steel (SS) [16][17][18][19][20][21][22][23][24][25][26][27][28] and to a lesser extent aluminum alloys. [29][30][31] However, to date, no focused study of the effect of Cu on the localized corrosion of Ni-Cr-Mo alloys has been published and the question remains as to whether its addition provides any value.…”
Section: Introductionmentioning
confidence: 99%
“…Коррозионное поведение, в том числе и питтинговая коррозия дуплексных сталей зависят от термообработки, микроструктуры, степени легирования, степени деформации [42][43][44][45][46][47][48] и т. д. Дуплексные стали отжигаются в области температур 600−1200 • C; во время отжига меняется соотношение α : γ-фаз и, кроме того, фазы обогащаются разными элементами. Cr и Mo обогащают ферритную α-фазу, а Ni, Mn и N -аустенитную γ-фазу, что сказывается как на общую, так и на локализованную коррозию [49].…”
unclassified